Investigating Measures to Revive Urban and Rural Tourism in The Post-Corona Era - Jamaleddin Honarvar (تحقیقات کاربردی علوم جغرافیایی)
The coronavirus pandemic has brought many challenges to countries around the world, and the tourism industry has not been left out. To address these challenges in the tourism industry, recovery and adaptation measures are a topic that requires more attention. The aim of the present study is to examine the measures to revive and recover urban and rural tourism in the post-corona era. The present study is applied in terms of its purpose and its method is mixed (qualitative and quantitative). The data and information collection tool is exploratory and in-depth interviews. The statistical population of the study is experts and specialists in the field of tourism, who conducted 50 in-depth interviews using non-probability sampling and purposefully. The qualitative method of grand theory, Strauss and Corbin method, was used to analyze the information. According to the experts, 32 concepts were identified for the revival and recovery of urban and rural tourism in the post-corona era; of these 32 indicators, 6 indicators were related to rural tourism, 6 measures to urban tourism, and 20 indicators to tourism of both urban and rural destinations. The effect of 2 indicators was also described as insignificant. The results showed that; compensation for tourism losses, prevention and control of the coronavirus pandemic, smart tourism, tax exemption and subsidy, revival of the tourism market, construction of quality tourism places, safety of accommodation and hospitality, improvement of health facilities, ensuring the safety of international tourism, restoring the trust of travelers, providing clear information to travelers, strengthening cooperation within and between countries, are the most important measures for the revival and recovery of urban and rural tourism. The results of this research can also be used to revive and recover urban and rural tourism in the post-corona era in other parts of the country.